Evaluation and Characterization of Plasma Sprayed Cu Slag-Al Composite Coatings on Metal Substrates. (25th December 2013) - Mantry, S.; Jha, B. B.; Satapathy, A.
Abstract : Copper slag is a waste product obtained during matte smelting and refining of copper. The present work explores the coating potential of copper slag by plasma spraying. This work shows that copper slag is eminently coatable. An attempt has been made in the present investigation to use the composites coatings of copper slag and Al powder in suitable combination on aluminium and mild steel substrates in order to improve the surface properties of these ductile metal-alloy substrates. When premixed with Al powder, the coating exhibits higher interfacial adhesion as compared to pure copper slag coatings. Maximum adhesion strengths of about 23 MPa and 21 MPa are recorded for the coatings of copper slag with 15 wt% of Al on aluminium and mild steel substrates, respectively. The input power to the plasma torch is found to affect the coating deposition efficiency and morphology of the coatings. It also suggests value addition of an industrial waste.